101 tough conversations to have with employees : a manager's guide to addressing performance, conduct, and discipline challenges - Falcone, Paul (AMACOM, 2009)
Inappropriate attire, lateness, sexually offensive behavior, not to mention productivity and communication issues ... these are just a few of the uncomfortable topics bosses must sometimes discuss with their employees. 101 Tough Conversations to Have with Employees offers realistic sample dialogues managers can use to facilitate clear, direct interactions with their employees, helping them sidestep potential awkwardness and meet issues head-on. This practical, solution-oriented book walks readers through some of the most common--as well as the most serious--employee problems they are likely to e.